Determinant Factors on Food Therapy in Autism Spectrum Disorder: A Synthesis of Literature Review - Dahal, Kabita (NPRC Journal of Multidisciplinary Research, 2025)
The increasing prevalence of Autism Spectrum Disorder (ASD) has spurred interest in alternative therapeutic approaches, including food therapy. This systematic literature review synthesizes existing research on the determinant factors influencing the effectiveness of food therapy in managing symptoms of ASD. The paper explores dietary interventions, such as gluten-free, casein-free (GFCF) diets, micronutrient supplementation, and probiotic use, and examines the biological, psychological, and social determinants that shape the efficacy of these interventions. The findings highlight the importance of personalized dietary plans, the role of the gut-brain axis, and the need for holistic approaches that consider both the physiological and psychosocial dimensions of ASD. Future research directions include longitudinal studies and clinical trials to establish clearer guidelines for food therapy in ASD management.